Mining activities and local economic development : evidence from Indonesian provinces - Jamal, Wiwoho; Irwan, Trinugroho; Evan, Lau (Inderscience Enterprises Ltd., 2022)
There has been a long debate on the benefits of mining activities to the local society, which is reflected in some economic indicators. In this study, we therefore empirically examine the impact of mining activities on the regional economy across provinces in Indonesia over the period of 2013–2017, ending up with 165 observations. We partially support our hypothesis by revealing that mining activities, measured by the total registered mining corporations in a province, are positively associated with local economic outputs proxied by regional GDP and regional GDP per capita. However, our study does not investigate the environmental impact of mining activities as highlighted by some previous studies.